Simazine Enhances Dark Fermentative H2 Production by Unicellular Halotolerant Cyanobacterium Aphanothece halophytica - Sunisa Pansook; Aran Incharoensakdi; Saranya Phunpruch (My University, 2022)
The halotolerant cyanobacterium Aphanothece halophytica is a potential H 2 producer that induces H 2 evolution under nitrogen deprivation. H 2 is mainly produced via the catabolism of stored glycogen under dark anaerobic condition. H 2 evolution is catalyzed by O 2 -sensitive bidirectional hydrogenase. The aim of this study was to improve H 2 production by A. halophytica using various kinds of inhibitors. Among all types of inhibitors, simazine efficiently promoted the highest H 2 production under dark conditions. High simazine concentration and long-term incubation resulted in a decrease in cell and chlorophyll concentrations. The optimal simazine concentration for H 2 production by A. halophytica was 25 µM. Simazine inhibited photosynthetic O 2 evolution but promoted dark respiration, resulting in a decrease in O 2 level. Hence, the bidirectional hydrogenase activity and H 2 production was increased. A. halophytica showed the highest H 2 production rate at 58.88 ± 0.22 µmol H 2 g −1 dry weight h −1 and H 2 accumulation at 356.21 ± 6.04 μmol H 2 g −1 dry weight after treatment with 25 µM simazine under dark anaerobic condition for 2 and 24 h, respectively. This study demonstrates the potential of simazine for the enhancement of dark fermentative H 2 production by A. halophytica .
Keywords: Halotolerance; Simazine; Algal biology and biofuel production